Trends in herbal pharmaceutical patent protection for Dairy industry: Perspective from Grassroots innovations - R K, Ravikumar; Dr Parul Sharma; R Rajeshwari; Praanjal Agarwal (Indian Journal of Dairy Science, 2023)
In accessing unique, innovative medicine(s) requirement of protecting pharmaceutical product patents is evolving among member states of World Trade Organisation. Accordingly, National Patent regime had amended Patent Act on Innovation and the study had identified patentability nature of indigenous dairy technologies in response to these requirements. Investigators had examined 28 herbal pharmaceutical patent grant(s) from grassroots innovators/outstanding knowledge holders. Patent applications were filed between 2007-2014, prosecution were held and accorded patent grant during 2019-2022. The study noted that Section 3 (d), (e) and (p) were principal factors involved while defending veterinary pharmaceutical patent applications.  About 46 percent did not have Section 3 (d) objections inferring these medicinal practices followed by dairy farming communities were unique. It was observed that majority of patent grants were in product category illustrating transformation of national patent regime from process patent to product-patent grant system.  Overall time taken for availing grant was about ten years with an average prosecution period of 2.6 years. Therapeutic efficacy, synergistic action and suitable claim amendments are pertinent features in responding to prosecution stages. These pharmaceutical product patents from social innovation are of interest to dairy industry. It is paramount to nurture this bottom-up approach for improvising sustainable dairy health service delivery system.